Implementation of it Strategy on E-Commerce in Business Competition As an Increase in Company Business Revenue (In MSMES) - Poppy Indri Hastuti; Sri Indah; Retno Ayu Dewi Novitawati; Elly Lestari (Return : Study of Management, Economic and Bussines, 2023)
A very effective way to spread knowledge is web development. With the advent of online supply channels that make it easy for potential clients to browse product details, request, or pay installments, web innovation has greatly impacted companies (web-based companies). This indicates that online deal exchangers have anticipated customers. Fair and legal levels of HR payouts, data, and concerns about the economy or organizations, companies, and public compensation are evaluated almost from one side of the planet to the other. The investigation in question is an emotional evaluation; the data used is mandatory and optional; collection, assessment, and documentation used in the data collection process; In addition, informal performance techniques are used in data request procedures. The use of online sales by the character of MSMEs Tempe Putra Ridhlo Chips as opposed to the character of MSMEs UD Mayla Jaya is proven to speed up transactions and facilitate the sale of goods to characters. To facilitate ordering goods or products for customers or clients, it can also be used in Ayam Geprek Ngamuk SMEs and Betis MSME Meatballs.